Perbedaan Motivasi WUS Melakukan Inspeksi Visual Asam Asetat (IVA) Sebelum dan Sesudah Diberikan Edukasi Berbasis Film Pendek Penelitian Dilakukan Di Desa Tiga Kabupaten Bangli - Ni Putu Sarina Kuntari Dewi; Ni Luh Putu Sri Erawati; Juliana Mauliku (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2021)
Visual Inspection Acetate Acid (VIA) is a screening for cervical cancer using 3-5% acetic acid. Motivation is an action that arises from someone to do something. Short films are stories less than 60 minutes that can be used as health education media. The purpose of this study is to determine differences motivation of women in fertile age to do VIA before and after given health education based on short film. This is pre-experimental research with one group pre-test post-test design. The samples are 42 women in fertile age that chosen by purposive sampling. Data were collected through questionnaires that given before and after the intervention. The research subjects were given health education by short film for once time during 10 minutes. The bivariate analysis used Wilcoxon test α 0.05. The median of motivation before given health education is 45.5 and after given health education by short film increase to 71 with ρ = 0,001 α (0,05) and Z value (-5.647). The conclusion shows there is motivation difference before and after given health education by short film. This intervention suggest given to fertile age women to increase motivation to do VIA.